Comparative effectiveness and safety of GATT with or without ABiC in patients with open-angle glaucoma - Zhang, Weijia; Wang, Yiwei; Chen, Xin; Zhang, Ke; Yang, Zhen; Sang, Jinghong; Zhang, Chun; Wang, Huaizhou (Frontiers in Medicine, 2025)
BackgroundThis is the first comprehensive comparison between gonioscopy-assisted transluminal trabeculotomy (GATT) and GATT combined with ab interno canaloplasty (ABiC) in patients with OAG.PurposeThe purpose of this study was to compare the efficacy and safety of gonioscopy-assisted transluminal trabeculotomy (GATT) combined with ab interno canaloplasty (ABiC) with those of GATT alone in patients with open-angle glaucoma (OAG).DesignThis was a retrospective, comparative case series.ParticipantsPatients with primary open angle glaucoma who underwent GATT (27 eyes in Group 1) or GATT + ABiC (26 eyes in Group 2) were included.MethodsOutcomes including intraocular pressure (IOP), glaucoma medications, and surgical complications were analyzed.Main outcome measuresSurgical success was defined in terms of IOP and medication use as follows: (1) a preoperative IOP > 21 mmHg and a postoperative IOP ≤ 21 mmHg with at least a 20% reduction from baseline with (qualified success) or without (complete success) glaucoma medications or (2) a preoperative IOP < 21 mmHg while taking 3 or more glaucoma medications and a postoperative IOP ≤ 21 mmHg with a reduction of more than two medications (qualified success) or with no medications (complete success).ResultsAt 12 months, the mean IOP was 14.8 ± 2.2 mmHg in Group 1 and 16.6 ± 2.3 mmHg in Group 2 (p = 0.008). The number of medications was 0.6 ± 1.0 in Group 1 and 0.9 ± 1.3 in Group 2 (p = 0.334). At 24 months, the mean IOP was 15.3 ± 2.0 mmHg in Group 1 and 15.5 ± 2.4 mmHg in Group 2 (p = 0.676). The number of medications was 0.5 ± 0.9 in Group 1 and 0.9 ± 1.1 in Group 2 (p = 0.197). The complete success rates were 63.0% in Group 1 and 50.0% in Group 2 (p = 0.16), and the qualified success rates were 81.5% in Group 1 and 76.9% in Group 2 (p = 0.51).ConclusionThe GATT procedure, with or without ABiC, is safe and effective in decreasing the IOP and the number of antiglaucoma medications used.